The relationship between internal environment of corporate entrepreneurship and innovation in private colleges in Perak - Wu, Jing Nan (Tanjong Malim, 2018)
The relationship between internal environment of corporate entrepreneurship and innovation in private colleges in Perak by Wu, Jing Nan